Balancing Microthrombosis and Inflammation via Injectable Protein Hydrogel for Inflammatory Bowel Disease. Issue 20 (7th May 2022) - Hong, Liwen; Chen, Gaoxian; Cai, Zhengwei; Liu, Hua; Zhang, Chen; Wang, Fei; Xiao, Zeyu; Zhong, Jie; Wang, Lei; Wang, Zhengting; Cui, Wenguo
Abstract: Emerging evidence indicates that a vicious cycle between inflammation and microthrombosis catalyzes the pathogenesis of inflammatory bowel disease (IBD). Over‐stimulated inflammation triggers a coagulation cascade and leads to microthrombosis, which further complicates the injury through tissue hypoxia and ischemia. Herein, an injectable protein hydrogel with anti‐thrombosis and anti‐inflammation competency is developed to impede this cycle, cross‐linked by silver ion mediated metal‐ligand coordination and electronic interaction with sulfhydryl functionalized bovine serum albumin and heparin, respectively. The ex vivo experiments show that the hydrogel, HEP‐Ag‐BSA, exhibits excellent self‐healing ability, injectability, biocompatibility, and sustained drug release. HEP‐Ag‐BSA also demonstrates anti‐coagulation and anti‐inflammation abilities via coagulation analysis and lipopolysaccharide stimulation assay. The in vivo imaging confirms the longer retention time of HEP‐Ag‐BSA at inflammatory sites than in normal mucosa owing to electrostatic interactions. The in vivo study applying a mouse model with colitis also reveals that HEP‐Ag‐BSA can robustly inhibit inflammatory microthrombosis with reduced bleeding risk. This versatile protein hydrogel platform can definitively hinder the "inflammation and microthrombosis" cycle, providing a novel integrated approach against IBD. Abstract : A microthrombosis and inflammation balancing protein hydrogel, HEP‐Ag‐BSA, is crosslinked by silver ion mediated metal‐ligand coordination and electronic interaction with sulfhydryl functionalized bovine serum albumin and heparin. This injectable hydrogel has prolonged retention at inflamed site, reduces the release of proinflammatory cytokines, and robustly inhibits microthrombosis, which exerts a definitive therapeutic effect on the pathogenesis of inflammatory bowel disease with guaranteed safety.